Fading roles of fictive kinship: mixed-blood racial isolation and United States Indian Policy in the Lower Missouri River Basin, 1790-1830 - Isenhower, Zachary Charles (Kansas State University, 2012)
On June 3, 1825, William Clark, Superintendent of Indian Affairs, and eleven representatives of the “Kanzas” nation signed a treaty ceding their lands to the United States. The first to sign was “Nom-pa-wa-rah,” the overall Kansa leader, better known as White Plume. His participation illustrated the racial chasm that had opened between Native- and Anglo- American worlds. The treaty was designed to ease pressures of proximity in Missouri and relocate multiple nations West of the Mississippi, where they believed they would finally be beyond the American lust for land. White Plume knew different. Through experience with U.S. Indian policy, he understood that land cessions only restarted a cycle of events culminating in more land cessions. His identity as a mixed-blood, by virtue of the Indian-white ancestry of many of his family, opened opportunities for that experience. Thus, he attempted in 1825 to use U.S. laws and relationships with officials such as William Clark to protect the future of the Kansa. The treaty was a cession of land to satisfy conflicts, but also a guarantee of reserved land, and significantly, of a “halfbreed” tract for mixed-blood members of the Kansa Nation. Mixed-blood go-betweens stood for a final few moments astride a widening chasm between Anglo-American and native worlds. It was a space that less than a century before offered numerous opportunities for mixed-blood people to thrive as intermediaries, brokers, traders, and diplomats. They appeared, albeit subtly, in interactions wherever white and Native worlds overlapped. As American Indians lost their economic viability and eventually their land, that overlap disappeared. White Plume’s negotiation of a reserve for his descendants is telling of a group left without a place. In bridging the two worlds, mixed-bloods became a group that by the mid-nineteenth century was defined as “other” by Anglo-American and Indians alike. This study is the first to track these evolving racial constructs and roles over both time and place. Previous studies have examined mixed-blood roles, but their identity is portrayed as static. This study contends that their roles changed with the proximity and viability of full-blood communities with which white officials had to negotiate.
Keywords: Native Americans; Mixed-blood; Lower Missouri River basin; American Indian policy; Native American land cession; American History (0337)